PENGARUH KOMPETENSI GURU, SUPERVISI KEPALA SEKOLAH, DAN MOTIVASI KERJA TERHADAP KINERJA GURU SEKOLAH LUAR BIASA (SLB) GUGUS TIMUR KABUPATEN BANTUL (JURNAL ILMIAH TUT WURI HANDAYANI, 2015)
The research aims to understand : (1) the influence of teacher’s competence, principal supervision and work motivation simultaneusly on the teacher’s performance of SLB Gugus Timur Bantul Regency. (2) the influence of teacher’s competence partially on the teacher’s performance of SLB Gugus Timur Bantul Regency (3) the influence of Principal Supervision partially on the teacher’s Performance of SLB Gugus Timur Bantul Regency. (4) the influence of work motivation partially on the teacher’s performance of SLB Gugus Timur Bantul Regency.The population of the research was whole teachers of SLB Gugus Timur Bantul Regency amounting to 141 teachers. Sampling in the study using technique of proportional random sampling of 103 teachers. The data collected by using questionaires form which had been tested to the 30 teachers and had been qualified of validity by the pearson correlation technique and reliability requirement with alpha’s cronbach technique. Data analysis techniques used were descriptive analysis, multiple regression and partial correlation, which was preceded by the prerequisite test analysis that were normality test, linearity test and multicollinearity test.The research results show that the teacher’s performance is at high category, teacher’s competence is at high category, principal supervision at high category and work motivation at high category. The result of multiple regression analysis shows 1) there is a positive and significant influence of the teacher’s competence, principals supervision and work motivation simultaneusly on the teacher’s performance of SLB Gugus Timur Bantul Regency. It means that the higher of teacher’s competence, principals supervision and work motivation, it will be the higher the performance of teachers. Results of partial correlation analysis shows 2). There is positive and significant influence of teacher's competence partially on the teacher’s performance of SLB Gugus Timur Bantul Regency. It means that the higher of teacher’s competence then will be increasingly higher of teacher's performance. 3.) there is positive and significant influence of principal supervision partially on the teacher’s performance of SLB Gugus Timur Bantul Regency. It means that the higher of principal supervision, then the higher of the teacher’s performance; and 4) there is positive and significant influence of work motivation partially on the teacher’s performance of SLB Gugus Timur Bantul Regency. It means that the higher of the work motivation then it will be the higher teacher’s performance.